2012
DOI: 10.1095/biolreprod.111.094946
|View full text |Cite
|
Sign up to set email alerts
|

Bovine DNA Methylation Imprints Are Established in an Oocyte Size-Specific Manner, Which Are Coordinated with the Expression of the DNMT3 Family Proteins1

Abstract: A subset of genes, known as imprinted genes, is present in the mammalian genome. Genomic imprinting governs the monoallelic expression of these genes, depending on whether the gene was inherited from the sperm or the egg. This parent-of-origin specific gene expression is generally dependent on the epigenetic modification, DNA methylation, and the DNA methylation status of CpG dinucleotides residing in loci known as differentially methylated regions (DMRs). The enzymatic machinery responsible for the addition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
81
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 53 publications
10
81
0
Order By: Relevance
“…S2). Similar to the mouse, exon 1 of the bovine SNRPN gene is hypermethylated on the maternal allele, with methylation acquisition in the oocyte being related to oocyte size (24,25). To date, no bovine SNRPN upstream exons appear in the UCSC Genome Browser, and application of 5′ RACE to bovine oocyte or hypothalamus RNA identified 5′ ends only in the vicinity of body exon 1 (Fig.…”
Section: Results Inmentioning
confidence: 95%
See 1 more Smart Citation
“…S2). Similar to the mouse, exon 1 of the bovine SNRPN gene is hypermethylated on the maternal allele, with methylation acquisition in the oocyte being related to oocyte size (24,25). To date, no bovine SNRPN upstream exons appear in the UCSC Genome Browser, and application of 5′ RACE to bovine oocyte or hypothalamus RNA identified 5′ ends only in the vicinity of body exon 1 (Fig.…”
Section: Results Inmentioning
confidence: 95%
“…Although maintained during somatic development, differential methylation at gDMRs is erased during fetal germ-cell development, particularly as primordial germ cells complete their migration to the fetal gonad (27). In female embryos, DMR methylation first appears shortly after birth in a DNMT3A-and DNMT3L-dependent process that is tied to oocyte growth (25,28,29). How specific regions are selected for methylation in oocytes is poorly understood, but substantial recent work indicates the essential role of transcription in setting methylation imprints in the female germline.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the treatment of calves with FSH and IGF1 prior to OPU renders the epigenetic status of the oocyte closer to that of the adult untreated oocyte. Recently, O'Doherty et al (2012) reported size-dependent methylation dynamics in growing bovine oocytes, possibly linking the acquisition of developmental competence with the acquisition of specific methylation.…”
Section: Discussionmentioning
confidence: 99%
“…During spermatogenesis and oogenesis, epigenetic modifications are established which are required for normal embryonic progression (Bourc'his et al, 2001;Rideout et al, 2001;O'Doherty et al, 2012). Reprogramming the maternal genome, through appropriate DNA methylation of differentially methylated regions (DMRs), is central in regulating genomic imprinting (Li et al, 1993), a process in which a small cohort of genes are exclusively expressed from a single allele, according to parent-of-origin (Preece and Moore, 2000).…”
Section: Reprogramming Of Dna Methylationmentioning
confidence: 99%